Clinical Teaching Effectiveness of Undergraduate Student Nurses in the United Arab Emirates - Mohamad AlMekkawi RN, PhD; Firas Qatouni RN, M.Ed; Hussam Al Amoor RN, MSN; Bassam Alayed RN, MQMS; Mohamad El Najm RN, PhD (SAGE Publishing, 2020)
Introduction Clinical supervision is a crucial aspect of developing nursing students' knowledge, skills, and professional attitudes. The characteristics of clinical instructors have a significant role in the progress and transition of students into their future professional roles. Objective The study aimed to examine the behaviors of effective clinical instructors as perceived by nursing students and faculty members in the UAE. Methods The study followed a cross-sectional quantitative research design to explore nursing students' and faculty members' perceptions of clinical instructors' effective behaviors that facilitate students' clinical practice. Data were collected from a convenience sample of 147 nursing students and 17 faculty members who completed an online version of the study survey at four nursing programs in the UAE. Results Students rated personality ( M = 4.96, SD = 1.91) and teaching ability ( M = 4.94, SD = 1.96) as the highest behaviors for effective clinical instructor. They perceived effective clinical instructor to be organized ( M = 5.19, SD = 1.88), shows self-confidence ( M = 5.16, SD = 1.84), able to answer questions ( M = 5.16, SD = 1.90), emphasizes what is crucial to learn ( M = 5.11, SD = 1.81), and takes responsibility for his/her actions ( M = 5.11, SD = 1.90). While faculty members perceived effective clinical instructor to encourage a climate of mutual respect ( M = 5.56, SD = 1.27), be approachable ( M = 5.47, SD = 1.32), demonstrates clinical skill and judgment ( M = 5.53, SD = 1.46), takes responsibility for his/her actions ( M = 5.53, SD = 1.37), and be a good role model ( M = 5.47, SD = 1.32). Conclusion Understanding clinical instructors' effective behaviors and supporting them during students' clinical experiences inspire a productive teaching-learning environment that is crucial to improve students' motivation, expand their learning opportunities and improve their hands-on skills.